Themed dissertation projects for taught MSc courses. Issue 3 (July 2016) - Renfrew, Alasdair; So, Daniel; Sloan, Robin; Gibson, Andrew
The School of Electrical and Electronic Engineering at the University of Manchester runs six taught MSc courses with a total cohort of over 200 students. The relatively short dissertation period requires rapid learning in the early stages. Themed projects were developed as a structure to facilitate these projects and enhance the student experience by separation of the expertise required for assistance in dealing with day-to-day technical problems from that of overseeing project strategy and progress. For the former process, doctoral and post-doctoral members of the school were selected and trained for the role of 'Mentor'. Their activity freed supervisors' time to concentrate on the critical aspects of student progress and project strategy. The themed project system has just completed its fourth year of operation and caters for approximately half of all the dissertation students in the school. The school also offers 'conventional' 1:1 supervised projects, principally for the smaller MSc courses, providing the MSc student with a choice of project system. However, all dissertations are individual and are assessed according to the same criteria. Evaluation has shown an improved level of student satisfaction with regard to the assistance habitually provided by members of the research group in which the projects take place.